Development of a robust attitude control for nonidentical rotor quadrotors using sliding mode control. (18th January 2018) - Promkajin, Nicom; Parnichkun, Manukid
This work proposes a novel development of sliding mode control (SMC) for quadrotor helicopters utilizing offset cancellation technique. Most of the works on sliding mode control for quadrotors assumed that all rotors were identical, but in fact, the rotors even from the same factory are not exactly the same in aerodynamics properties. In addition, rotor deformation due to shock or heavy usage during operation may cause changes in parameters such as lift and drag coefficients, and so on, which, lead to offset error in the responses of attitude control. By applying the proposed offset cancellation technique to the sliding mode control, the attitude error is forced to have a zero average. The proposed controller is used to control attitude and position of a quadrotor helicopter which is composed of four direct current (DC) brushless motors to generate lift forces independently. Performance comparison with the other control algorithms such as the proportional–integral–derivative controller and the conventional sliding mode control is simulated and experimented on two real quadrotor platforms and results are discussed.